Development of a Figural Creativity Assessment Instrument Based on Torrance Tests of Creative Thinking (TTCT) for Elementary School Students - Attar Mirza; Agung Hastomo; Firmansyah Firmansyah (Journal of Educational Sciences, 2026)
This study aimed to develop a figural creativity assessment instrument based on the Torrance Tests of Creative Thinking (TTCT) for elementary school students and to examine its validity and reliability. The research employed a Research and Development approach using the 4D model, consisting of define, design, develop, and limited disseminate stages. The participants were elementary school students in Yogyakarta. A limited trial involved 16 students, while the field test involved 106 students. Data were collected using the developed figural creativity test, supported by expert validation sheets and student response questionnaires. Content validity was evaluated through expert judgment, internal validity was analyzed using Spearman rank correlation, and inter-rater reliability was examined using the Intraclass Correlation Coefficient (ICC). The results indicated that the instrument demonstrated high feasibility in psychological, linguistic, and instructional aspects. Internal validity analysis showed significant positive correlations among stimuli and creativity dimensions. Inter-rater reliability showed good agreement for fluency (ICC = 0.646), flexibility (ICC = 0.754), and elaboration (ICC = 0.779), while originality showed lower agreement (ICC = 0.194). Overall, the developed instrument is valid and reliable for assessing figural creativity in elementary school students, although further refinement of originality scoring procedures is recommended.